2013 IEEE International Conference on Communications (ICC) 2013
DOI: 10.1109/icc.2013.6655009
|View full text |Cite
|
Sign up to set email alerts
|

Degrees-of-freedom for the 4-user SISO interference channel with improper signaling

Abstract: It has been recently shown that for the 3-user singleinput single-output (SISO) interference channel with constant channel coefficients, a maximum of 1.2 degrees-of-freedom (DoF) are achievable using linear interference alignment schemes when improper (a.k.a. asymmetric) Gaussian signaling is applied. In this paper, we study the 4-user SISO interference channel and provide inner and outer bounds for the total number of DoF achievable for this channel. We prove that at least 4 3 DoF are achievable for the 4-use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 10 publications
3
36
0
Order By: Relevance
“…4 that improper Gaussian signaling outperforms the proper Gaussian counterpart in the strong interference regime, especially when the interference link gain |h 12 | is large. Although proper Gaussian signaling is also able to avoid performance degradation from excessive interference by letting S 2 to remain silent when the interference link gain |h 12 | is large, the extra dimension provided by improper Gaussian signaling is generally superior for the system sum-rate. This is achieved by adjusting the interference and the desired signal to be orthogonal to each other, hence eliminating the influence of the interference while still allowing S 2 to transmit.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 that improper Gaussian signaling outperforms the proper Gaussian counterpart in the strong interference regime, especially when the interference link gain |h 12 | is large. Although proper Gaussian signaling is also able to avoid performance degradation from excessive interference by letting S 2 to remain silent when the interference link gain |h 12 | is large, the extra dimension provided by improper Gaussian signaling is generally superior for the system sum-rate. This is achieved by adjusting the interference and the desired signal to be orthogonal to each other, hence eliminating the influence of the interference while still allowing S 2 to transmit.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…This higher achievable DoF using improper signaling is due to its ability to control the interference signal dimension, and it is one form of interference alignment [11]. The DoF results have also been extended to IC with larger number of users, such as 4-user IC, which is shown to have 4/3 DoF per user [12]. Beyond the DoF analysis for IC, [13] showed that improper signaling with widely linear receiver in point-to-point Multiple Input Multiple Output (MIMO) channels can reduce the bit error rate as compared to proper signaling.…”
mentioning
confidence: 99%
“…The same applies in the Gaussian MIMO interference channel (IC), where IGS has been shown to: i) obtain larger degrees of freedom, i.e. slope of the sumrate as a function of the signal-to-noise ratio (SNR) at the high SNR regime, [3][5] [13] and ii) improve the known achievable rates when interference is treated as noise under certain MIMO configurations [4][14] [15] and under coexistence of linear and widely linear transceivers in MIMO systems [16] [17]. In addition, the positive benefits of IGS have been reported in terms of achievable rates [18] and outage probabilities [19] for underlay cognitive radio systems.…”
Section: Introductionmentioning
confidence: 99%
“…They considered a single-antenna three-user interference channel with constant channel extensions and showed that the number of degrees of freedom (DoF), which is the number of interference-free signals that can be transmitted, was larger when users transmit improper signals as opposed to proper ones. Similar DoF results were derived for the four-user interference channel in [14]. After that, a number of new works has emerged, and the payoffs of improper signaling have been revealed for different multiuser scenarios such as the interference channel [3][4][5]15], Z-interference channel [6,[16][17][18], broadcast channels with linear precoding [19,20], underlay and overlay cognitive radio networks [7,8,21] and relay channels [22,23].…”
Section: Introductionmentioning
confidence: 50%